The Effectiveness of Using E-Comics as a Learning Medium for Tsunami Disaster Mitigation at SMA 1 Pertiwi Padang - Indriana; Ernawati; Arnita Fitri (Jurnal Penelitian Pendidikan IPA, 2025)
Padang City, located on the west coast of Sumatra Island, is one of the Region most vulnerable to tsunami disasters due to its position along the subduction zone between the Indo-Australian and Eurasian plates. This study aims to determine the effectiveness of using E-Comics as a learning medium for tsunami disaster mitigation at SMA 1 Pertiwi Padang City. The research employed a quasi-experimental method with a Non-Equivalent Group Design, involving two groups: the experimental class (XI IPS 2) using E-Comics and the control class (XI IPS 1) using conventional textbooks. Data were collected through questionnaires and documentation, and analyzed using normality, homogeneity, and t-tests with the aid of SPSS version 22.0. The results showed that the data were normally distributed and homogeneous, and there was a significant difference between the learning outcomes of the experimental and control classes, with a significance value of 0.95 > 0.05 and a t-value of 7.45. The average pre-test and post-test scores in the experimental class increased from 53.40 to 87.10, while the control class increased from 51.87 to 61.53. These findings indicate that using E-Comics effectively enhances students’ understanding and motivation in learning tsunami disaster mitigation material. Therefore, E-Comics can serve as an innovative alternative in geography learning, particularly in disaster-prone areas, to improve students’ literacy and preparedness for disasters.